Folgen der Grundwasserabsenkung im Moerser Land. Auswirkungen auf das Wechselwirkungsgefüge der Geofaktoren und die landwirtschaftliche Nutzung - Hofmann, Manfred (ERDKUNDE, 1975)
About one hundred years ago the “Moerser Land, a flat area of quarternary sediments on the middle lower Rhine, was very wet. Much surface water ran through it and seldom was the ground-water more than two metres below the surface. Ecological interrelationships and operations as well as the differentiations of the agrarian landscape had been delicately adapted to the high water-table. When coal mining rapidly spread in this region, particularly after the turn of the century, subsidence occurred in some smaller areas, under which mining operations were going on. As the subsiding areas were soaked with water or even flooded, something had to be done to drain them. Ditches were dug and pumps installed to lead away the water. Thus it could be brought to the optimum level in the subsiding areas, but at the same time the distance between water-table and surface was increased in larger parts of the region. The lowering of the ground-water table was favoured by the rapid vertical erosion of the Rhine (about 4 cm per year between 1900 and 1950) and its falling water-level as well as the immense exploitation of ground-water by industry and population in recent years. Decisive changes have been brought about by the falling water-table. Above all soil and vegetation have quickly reacted. But so has agricultural utilisation. The former interaction of geo-factors has been changed. Once recessive factors have turned out to be dominant, effecting and regulating nicely differing interactions, so that the once largely homogeneous landscape has developed into three different ones that can be told from each other even physiognomically.